Pengelolaan Sarana Prasarana Terhadap Efektivitas Kerja Pegawai Di Kantor BNNP Sumut - Nusroh Afifah; Juliana Nasution (Postgraduate, University of Mataram, 2022)
Management of facilities and infrastructure is not the main focus in the efficiency of the work of employees in the Office of the National Narcotics Agency of North Sumatra Province, infrastructure only acts as a means of assisting employees to carry out all activities and work in the office. The management of facilities and infrastructure at the North Sumatra BNNP Office is quite optimal. The existence of office facilities and infrastructure as a form of effort in increasing employee motivation and as a means of supporting employee work activities, it is very necessary to manage good office structures and infrastructure. In the management of office structures and infrastructures, it is not only the duty of General Affairs (GA), but includes all existing employees, so that the facilities and infrastructure that will be used will operate effectively and efficiently in accordance with the implementation procedures